ROMSKI MODEL SPRAWIEDLIWOŚCI NAPRAWCZEJ - Lorek, Dominika (Wydział Prawa i Administracji UAM, 2012)
Metody alternatywnego rozwiązywania sporów (ADR) są w Polsce wciąż rzeczą nową i wymagającą udoskonalenia. Poszukując wzorców realizacji idei sprawiedliwości naprawczej w prawie karnym, warto pochylić się nad zwyczajowymi „sądami” romskimi funkcjonującymi we współczesnej Europie. Autorka zarysowuje mało znaną szerszemu odbiorcy historię i obyczajowość polskich Romów. Zasadniczą część artykułu poświęca opisowi funkcjonowania tak zwanych sądów romskich. Analizuje zgodność ich założeń z koncepcją kręgów sprawiedliwości naprawczej poprzez ukazanie modelu romskiego na tle innych opisywanych w literaturze przedmiotu.

*The methods of alternative dispute resolution (ADR) are still a novelty in Poland and they need to be improved. While seeking the patterns of implementation of the idea of restorative justice in criminal law, it may be noteworthy to refer to the customary Romani ‘courts’ that exist in modern Europe. In the paper, the Authoress outlines the history and customs of Polish Roma Gypsy people, still little known to the wider society. An essential part of the paper is devoted to the description of the functioning of so-called Romani courts. The conformity of their assumptions with the conception of circle models of restorative justice through a demonstration of Romani model against the background of other models described in the literature is then analysed.
THE ROMANI MODEL OF RESTORATIVE JUSTICE
Keywords: sprawiedliwość naprawcza; restorative justice; Romowie; Romani people; Cyganie; Gypsies; sąd romski; Romani court; kris, celo, romanipen